The Influence of Physical Activity on Cognitive Function and Academic Performance: A Meta-Analysis in Education-al Settings - Didik Cahyono; Gyta Krisdiana Cahyaningrum; Muhammad Sukron Fauzi; Naheria Naheria (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Physical activity has been recognized as an important factor in improving students' cognitive function and academic achievement. However, there is uncertainty regarding the type and intensity of physical activity that is most effective in the educational context. This study aims to analyze the relationship between physical activity, cognitive function, and academic achievement through a meta-analysis approach, and to identify moderating factors that influence the relationship. This study used a meta-analysis method by collecting data from studies published in peer-reviewed journals. The data collection process followed the PRISMA guidelines, and the analysis was conducted using Comprehensive Meta-Analysis (CMA) to evaluate heterogeneity and moderation effects. The results showed that there was a significant positive relationship between physical activity and improvements in cognitive function and academic achievement. Moderate to high-intensity aerobic activity was shown to be more effective than light activity. The findings also showed that elementary school-aged children gained greater cognitive benefits than students at higher levels of education. This study emphasizes the importance of integrating physical activity into the educational curriculum to improve academic outcomes. These findings make a significant contribution to the development of evidence-based educational policies and support more interactive teaching practices.